The Prognostic Significance of Metastatic Nodal Size in Non-surgical Patients With Esophageal Squamous Cell Carcinoma - Zhao, Zongxing; Zhang, Yanan; Wang, Xin; Wang, Peiliang; Geng, Xiaotao; Zhu, Liqiong; Li, Minghuan (Frontiers in Oncology, 2020)
ABSTRACT Background: The present study aimed to determine the prognostic value of the size of metastatic lymph node (LN) in non-surgical patients with esophageal squamous cell carcinoma (ESCC). Methods: Three hundred seventy-six ESCC patients treated with definitive (chemo-)radiotherapy from January 2013 to March 2016 were reviewed. We analyzed potential associations of metastatic nodal size with responses, patterns of failure, and survival. Log-rank testing and Cox proportional hazards regression models were used to assess the impact of the clinical factors on survival. Results: The 3-year over survival (OS) rates following a median follow-up of 28.2 months were 53.2%, 46.2%, 35.5%, and 22.7% for the N0 group, the >0.5 to ≤1 cm group, the >1 to ≤2 cm group, and the >2 cm group, respectively. The progression-free survival (PFS) rates for 2 years were 50.9%, 44.2%, 26.6%, and 23.4% for the N0 group, the >0.5 to ≤1 cm group, the >1 to ≤2 cm group, and the >2 cm group, respectively. The objective response rates (ORR) for the 280 patients with metastatic LNs were 43.1% for the LN >0.5 to ≤1 cm group, 46.9% for the LN >1 to ≤2 cm group, and 25.5% for the LN ≥2 cm group. The LN >2 cm group had the worst ORR of the 3 groups with LNs. Gross tumor volume (GTV) failure was the most common failure pattern, followed by distant failure and out of GTV LN failure, with incidences of 47.9% (180 of 376), 42% (158 of 376), and 13.8% (52 of 376), respectively. Nodal size correlated statistically with GTV failure and distant failure but not with out-of-GTV nodal failure. After adjusting for age, sex, T category, Primary tumor location and CRT, the size of metastatic LNs was an independent prognostic factor for OS and PFS in multivariate analyses. Conclusions: Nodal size is one of prognostic factors for non-surgical patients with ESCC and correlated statistically with GTV failure and distant failure.